2020
DOI: 10.1021/acs.jpcb.0c06046
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Nonlinear Optical Properties of Solvated para-Nitroaniline Predicted by an Electrostatic Discrete Local Field Approach

Abstract: A general computational protocol for accurate predictions of nonlinear optical (NLO) properties of solvated molecules based on the rigorous local field (RLF) approach taking all relevant effects into account is presented. para-Nitroaniline (pNA) was taken as a model NLO system dissolved in cyclohexane, tetrahydrofuran, and 1,4-dioxane. Molecular dynamics (MD) simulations employing either non-polarizable or polarizable force fields were used to generate representative sets of structures of the solutions. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 135 publications
0
6
0
Order By: Relevance
“…Though the model adopted here performed well, as a perspective with respect to the level of approximation, it would be interesting to investigate approaches where the effects of the surroundings are described in TD-DFT calculations by using a structured or explicit environment, using an electrostatic discrete local field approach, as it was recently demonstrated. 41 Finally, this work also demonstrated that the intramolecular descriptors related to π conjugation within the cations are not linearly correlated to the NLO responses, which might call for the development of new computational approaches such as machine learning 42 to unravel the interplay between structural parameters and NLO properties.…”
Section: Discussionmentioning
confidence: 92%
“…Though the model adopted here performed well, as a perspective with respect to the level of approximation, it would be interesting to investigate approaches where the effects of the surroundings are described in TD-DFT calculations by using a structured or explicit environment, using an electrostatic discrete local field approach, as it was recently demonstrated. 41 Finally, this work also demonstrated that the intramolecular descriptors related to π conjugation within the cations are not linearly correlated to the NLO responses, which might call for the development of new computational approaches such as machine learning 42 to unravel the interplay between structural parameters and NLO properties.…”
Section: Discussionmentioning
confidence: 92%
“…44 In an alternative scheme, the polarization due to the surrounding solvent molecules was included via a self-consistent local field that is determined from the interactions between the molecular multipoles and their polarizabilities, which were evaluated beforehand at QM levels. 45 This electrostatic dressing field (and its gradient) was combined with classical MD simulations employing either nonpolarizable or polarizable force fields, and used to evaluate the EFISHG and HRS properties of the paranitroaniline molecule in cyclohexane, tetrahydrofuran and 1,4dioxane solutions. The macroscopic susceptibilities were subsequently evaluated from the molecular responses using classical electrostatic interactions schemes.…”
Section: Dyes In Solutionmentioning
confidence: 99%
“…This strategy was recently coupled to classical MD simulations in order to evaluate the HRS response of organic acids in aqueous solution . In an alternative scheme, the polarization due to the surrounding solvent molecules was included via a self-consistent local field that is determined from the interactions between the molecular multipoles and their polarizabilities, which were evaluated beforehand at QM levels . This electrostatic dressing field (and its gradient) was combined with classical MD simulations employing either nonpolarizable or polarizable force fields, and used to evaluate the EFISHG and HRS properties of the para-nitroaniline molecule in cyclohexane, tetrahydrofuran and 1,4-dioxane solutions.…”
Section: Case Studiesmentioning
confidence: 99%
“…This sequential MD + QM (or MD + DFT) scheme 23–26 has been previously employed to characterize the SH responses of various organic species in solution, including photochromic compounds. 27–35 For example, it was shown to drastically improve the description of the first hyperpolarizability contrast between the open and closed forms of switchable indolino-oxazolidine derivatives. 28…”
Section: Introductionmentioning
confidence: 99%